Ossification of the Interosseous Membrane of the Leg in a Football Player: Case Report and Review of the Literature - Roberto Postacchini; Stefano Carbone; Marco Mastantuono; Carlo Della Rocca; Franco Postacchini (Case Reports in Orthopedics)
Introduction. We report a case of ossification of the interosseous membrane (OIM) of the leg in a football player who had no history of severe local traumas. A review of the literature of the OIM of the leg in athletes was also carried out. Case Report. A 38-year-old Caucasian male patient complained of pain on lateral aspect of the leg when playing football. Pain progressively worsened until he had to stop the sporting activity. Radiographs, and then CT and MRI, showed OIM in the middle third of the left leg. MRI showed inflammation of tibia periosteum and bone adjacent to the ossification, which was then excised. Two months after surgery the patient returned to play football. Conclusion. A thorough analysis of the literature revealed three types of OIM of the leg in athletes. Type I usually occurs after a syndesmosis ankle sprain, Type II appears to result from a tibia fracture, and Type III, of which only one fully recorded case has been published, is probably caused, as in our patient, by repetitive minor traumas to the leg. Awareness of the existence of Type III OIM can avoid erroneous diagnoses leading to useless investigations and treatments.